The relationship and influence of leadership style towards knowledge management activities - Idris, Ahmad Sufi Alawi; Jamaludin, Adnan; Abdul Rahman, Abd. Latif; Mislan, Ayuffeirah (2016)
The study emphasized that the concept of leadership is not confined just to a certain group of individual that is appointed by an organization to handle administrative matters.Researchers from the epistemology of leadership believed that the term leaders refer to everyone from the CEO and board of directors down to unofficial opinion leaders who work on the factory floor.Therefore, the purpose of this paper is to propose a framework to identify the individual leadership style of employees regardless of their position within the organization, which is believed to be directly influencing the richness of their daily knowledge management activities in the organization.